Our silence is abusing our kids : what can our communities do about child sexual assault - Women's Legal Resources Centre (N.S.W.). (Lidcombe, N.S.W. : Women's Legal Resources Centre Ltd trading as Women's Legal Services NSW, 2004)
An Aboriginal response to child sexual assault in their communities.
Keywords: Sexually abused children -- Rehabilitation -- New South Wales; Community organisations - Social welfare; Sex relations - Child sexual abuse; New South Wales (NSW); Menindee (NW NSW SI54-03); Wilcannia (NW NSW SH54-16)